2015
DOI: 10.1074/jbc.m114.590364
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Transient Receptor Potential Channel 5 Reverses 5-Fluorouracil Resistance in Human Colorectal Cancer Cells

Abstract: Background: Resistance to 5-fluorouracil leads to the failure of chemotherapy for colorectal cancer. Results: Suppressing TrpC5 expression decreased nuclear ␤-catenin accumulation, reduced the induction of ABCB1, and reversed 5-fluorouracil resistance. Conclusion: TrpC5 is essential in ABCB1 induction and drug resistance in human colorectal cancer cells. Significance: These findings may help develop a novel target for overcoming resistance to chemotherapy in colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 40 publications
2
79
0
Order By: Relevance
“…It has been reported that the expression of P-gp is up-regulated in 5-FU chemoresistant colon cancer cells [22]. The failure of 5-FU treatment of HCT 116 p53−/− cells in condition of pL3 silencig (MTT, TMRE and clonogenic assay and [15]) prompted us to investigate whether the molecular mechanisms underlying L3-mediated enhancement of 5-FU activity involved alteration in P-gp production.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the expression of P-gp is up-regulated in 5-FU chemoresistant colon cancer cells [22]. The failure of 5-FU treatment of HCT 116 p53−/− cells in condition of pL3 silencig (MTT, TMRE and clonogenic assay and [15]) prompted us to investigate whether the molecular mechanisms underlying L3-mediated enhancement of 5-FU activity involved alteration in P-gp production.…”
Section: Discussionmentioning
confidence: 99%
“…1C), which indicated that the increase of total b-catenin expression led to the nuclear accumulation of b-catenin rather than inducing the phosphorylation of PTEN, leading to activation of PI3K/Akt signaling, resulting in the stabilization and nuclear translocation of b-catenin [24]. It has been reported that b-catenin translocates to and accumulates in the nucleus, where it activates the expression of T-cell factor/lymphoid enhancer factor (TCF/LEF), and promotes the expression of downstream target genes, such as c-myc, MMP-7, COX-2, MRP1, and cyclin D1 [25]. To test this possibility in our model, we assessed the protein expression of c-myc and cyclin D1 while treating transfected cells with PTX, and found that they increased with increasing PTX concentration (Fig.…”
Section: Induction Of Ctnnb1 Ires Activity and Downstream Factor Protmentioning
confidence: 99%
“…For example, TrpC1 and TrpC3 are involved in the proliferation of breast and ovarian cancer cells, respectively (16,17), while TrpC6 is involved in the proliferation of liver and prostate tumor cells (18,19). Previously, we found that TrpC5-mediated Ca 2+ -entry induced chemoresistance in CRC via activating the Wnt/β-catenin signaling pathway (20), and the latter was demonstrated to upregulate glycolysis in CRC (21). To date, there is still no study concerning the role of Ca 2+ signaling in the regulation of glycolysis, and the detailed mechanism by which TrpC5 induces chemoresistance also deserves exploration.…”
Section: Introductionmentioning
confidence: 99%